Finely Ground Camellia sinensis (L.) Kuntze leaves (Matcha) Inhibits Porphyromonas gingivalis Growth and therefore may be Useful to Control Periodontitis - Cock, Ian E (Pharmacognosy Communications)
Periodontal (gum) disease is a serious disease that may result in bones retracting from teeth, loss of teeth (or bone) and halitosis (bad breath). In its early stages (gingivitis), the gums may become swollen, inflamed and may bleed. Numerous plants have been used in traditional medicine systems to prevent and treat periodontal disease, with many plants highlighted for their efficacy.1-4 A recent study reported that matcha tea (prepared from finely ground Camellia sinensis (L.) Kuntze powder) inhibits the growth of the bacterium Porphyromonas gingivalis, which is one of the main bacteria that cause gingivitis and periodontitis.5 Indeed, MIC values as low as 125 μg/mL were reported against this bacterium, indicating that the extract is a potent inhibitor. The matcha extract also inhibited the growth of other bacteria associated with periodontal disease, including Prevotella nigrescens and Fusobacterium nucleatum. Interestingly, the matcha extract had little or no effects against multiple strains of commensal oral bacteria. The ability to inhibit the pathogenic bacteria whilst not otherwise adversely affecting the oral microbiome further highlights the potential of matcha extracts as mouthwashes to prevent and treat periodontal disease.